Damage formation, fatigue behavior and strength properties of ZrO[2]-based ceramics; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Kozulin A. A.; Narikovich A. S.; Kulkov S. N. Sergey Nikolaevich; Leitsin V. N.; Kulkov S. S. (2016, 2016)
Title screen